Enhancing mechanical properties of waste expanded polystyrene composites through varied coupling agents and wood powder formulations - Budiyantoro, Cahyo; Yudhanto, Ferriawan (Jurnal Polimesin, 2023)
This study investigates Wood Plastic Composites (WPCs) by incorporating waste Expanded Polystyrene (EPS) and various wood powder reinforcements. The mechanical properties of WPCs play a pivotal role in sustainable material development. Our research delves into the effects of different treatments on wood powders and their interactions with the polymer matrix.Pine, teak, and silk tree wood powders underwent alkali immersion and coupling agent treatments. The ensuing composites underwent rigorous testing, including flexural strength, hardness, and impact resistance assessments.The findings underline the complex factors governing WPC mechanical properties. Pine-based WPCs, reinforced with pine wood powder and subjected to alkali treatment, exhibited the highest flexural strength at 29.56 MPa, whereas the lowest flexural strength of 14.65 MPa was observed in WPCs reinforced with alkali-treated teak wood powder. The highest impact strength quantified at 2.54 kJ/cm², was found in untreated pine wood powder-based WPC. In contrast, the lowest impact strength was identified in teak wood powder-based WPC treated with alkali.